2020
DOI: 10.1002/cbdv.202000055
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Anti‐Alzheimer's Disease‐Related Activities of a Functional Oil from the Edible Seaweed Hizikia fusiforme

Abstract: Cholinergic disorder, oxidative stress, and neuroinflammation play important roles in the pathology of Alzheimer's disease. To explore the healthy potential of the edible seaweed Hizikia fusiforme on this aspect, a functional oil (HFFO) was extracted from this alga and investigated on its constituents by gas chromatography‐mass spectrometry (GC/MS) in this study. Its anti‐Alzheimer's related bioactivities including acetylcholinesterase (AChE) inhibition, antioxidation, and anti‐neuroinflammation were evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…Yang et al [ 69 ] discovered that the main components of the lipid-soluble subfraction of the H. fusiformis functional oil (HFFO) were tetradecanoic acid (11%), palmitic acid (37.80%), 9-hexadecenoic acid (2.67%), phytol (33.21%), and arachidonic acid (15.32%) ( Figure 6 ). These components have anti-neuroinflammatory properties that can help prevent Alzheimer’s disease [ 69 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Yang et al [ 69 ] discovered that the main components of the lipid-soluble subfraction of the H. fusiformis functional oil (HFFO) were tetradecanoic acid (11%), palmitic acid (37.80%), 9-hexadecenoic acid (2.67%), phytol (33.21%), and arachidonic acid (15.32%) ( Figure 6 ). These components have anti-neuroinflammatory properties that can help prevent Alzheimer’s disease [ 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…Yang et al [ 69 ] discovered that the main components of the lipid-soluble subfraction of the H. fusiformis functional oil (HFFO) were tetradecanoic acid (11%), palmitic acid (37.80%), 9-hexadecenoic acid (2.67%), phytol (33.21%), and arachidonic acid (15.32%) ( Figure 6 ). These components have anti-neuroinflammatory properties that can help prevent Alzheimer’s disease [ 69 ]. Generally, oil extracts from terrestrial plants have been shown to possess several biological properties, including anti-inflammatory, neuroprotective, and antioxidant properties, as well as the ability to increase the bioavailability of other drugs [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, 111 combined to a site with the α-helical motif quite far from the active pocket. However, its docked pose showed even lower CDOCKER interaction energy (−50.36 kcal/mol) when compared to 110 , thus explaining its stronger anti-AChE activity [ 68 ].…”
Section: Marine-derived Compounds That Inhibit Acetylcholinesterase (Ache) and Butyrylcholinesterase (Buche) Activitiesmentioning
confidence: 99%
“…But the study is rare on the brainhealth value of its oil. Previously, we reported that the Hizikia fusiforme functional oil (HFFO) contained arachidonic acid (ARA, one of the two main PUFAs in the brain) (20.54%), 11,14,17-eicosatrienoic acid (ETrA) (19.53%), phytol (6.55%) (Bazinet and Layé, 2014), and other molecules displayed in vitro acetylcholinesterase inhibitory and nitroxide scavenging activity (Yang et al, 2020). However, the in vivo effect remains unclear.…”
Section: Introductionmentioning
confidence: 99%